The effect of ginsenoside Rg5, isolated from black ginseng, on heart failure in zebrafish based on untargeted metabolomics. (January 2021) - Liu, Junli; Liu, Yunhe; Lin, Hongqiang; Zhou, Baisong; Yu, Hui; Li, Le; Wang, Caixia; Li, Xinyu; Li, Pingya; Liu, Jinping; Hao, Xiuhua
Graphical abstract: Highlights: Ginsenoside Rg5 displayed excellent ACE inhibitory activity in vitro . Ginsenoside Rg5 exhibited good activity in zebrafish heart failure model. The preliminary mechanism of Rg5 on heart failure was studied by using untargeted metabolomics. Abstract: Heart failure (HF), with a high fatality rate, is seriously harmful to human health. Ginsenoside Rg5 (Rg5) is the major active component in black ginseng. The effect and mechanism of Rg5 on HF were investigated for the first time. Firstly, the in vitro angiotensin-converting enzyme (ACE) inhibitory activity was evaluated. Then, the verapamil-induced zebrafish HF model was used to assay the effect of Rg5. Finally, the untargeted metabolomics based on UPLC-QTOF-MS was applied to explore the latent mechanism by analyzing the metabolic perturbation. The results showed that Rg5 had a similar ACE-inhibitory activity (IC50  = 0.124 μM) to the reference drug enalapril. Rg5 could dramatically improve cardiac function in a dose-dependent manner. A total of 22 differentiated metabolites and 8 perturbed metabolic pathways were identified. In summary, this study indicated that Rg5 could be a potential agent for protecting heart function in the clinical treatment of heart failure.